Comparison of Medium-term Outcomes of Living Kidney Donors With Longitudinal Healthy Control in the United Kingdom. Issue 3 (March 2020) - Krishnan, Nithya; Mumford, Lisa; Lipkin, Graham; Gill, Paramjit; Fletcher, Simon; Dasgupta, Indranil; Ryan, Ronan; Raymond, Neil T.
Abstract : Background: Understanding the outcomes and risks for live kidney donors (LD) is increasingly important; this study investigated all-cause mortality and morbidity outcomes of LD compared with a healthy cohort. Methods: Live donor dataset was obtained from the UK Transplant Registry and a comparator nondonor cohort selected from The Health Improvement Network (THIN) database, a UK primary healthcare database. All LD from January 1, 2001, to December 31, 2013, were included, with follow-up until December 31, 2016. Results: There were 9750 LD and 19 071 THIN participants. Median follow-up (interquartile range) for LD was 8.4 (6.0–11.3) years and for THIN was 5.4 (2.6–8.5) years. In up to 15 years, follow-up end-stage renal disease was observed in 1 LD versus 7 THIN ( P = 0.280). Nine LD had estimated glomerular filtration rate of <30 mL/min/1.73 m 2 versus 43 in THIN ( P = 0.012), but no statistically significant difference in adjusted logistic regression analyses. Risk of diabetes mellitus, depression, and cardiovascular disease was significantly higher for THIN cohort in adjusted analyses. The risk of hypertension was higher for LD at 5 years but was not significantly different in fully adjusted analyses at 10 years. There were 68 deaths in LD and 485 in THIN over the follow-up period, with significant difference in mortality favoring LD ( P < 0.001). Conclusions: The medium-term morbidity and mortality outcomes of live donors in comparison with a healthy cohort suggest that live donation is not associated with excess mortality, end-stage renal disease, or morbidity, in at least 10 years follow-up. Abstract : Supplemental Digital Content is available in the text.